2016
DOI: 10.30979/rev.abeno.v15i3.160
|View full text |Cite
|
Sign up to set email alerts
|

Feedback no processo de aprendizagem: percepção dos estudantes de Odontologia em uma universidade brasileira

Abstract: O objetivo do estudo foi analisar a opinião dos estudantes do ciclo profissionalizante do curso de Odontologia da Universidade Federal do Espírito Santo (UFES) e discutir a respeito de assuntos que envolvem a prática do feedback no processo ensino-aprendizagem. Trata-se de um estudo exploratório, de abordagem qualitativa, no qual foram aplicados questionários semiestruturado e entrevista aos alunos do 7º ao 10º período do curso de odontologia. Os dados revelaram que os alunos tendem a valorizar feedback, afirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
2
0
1
Order By: Relevance
“…However, what has been observed in the perception of a substantial segment of the students is the idea that the initial contact with the basic subjects does not correspond to the expectation regarding the knowledge of the university and the course. Other study corroborates this finding, in which the students who composed the study reported higher learning significance in the vocational cycle [3]. This situation gave rise to the category "Disarticulation of the disciplines of the Basic with the vocational cycle," which could be identified from observations of the students, such as the following:…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…However, what has been observed in the perception of a substantial segment of the students is the idea that the initial contact with the basic subjects does not correspond to the expectation regarding the knowledge of the university and the course. Other study corroborates this finding, in which the students who composed the study reported higher learning significance in the vocational cycle [3]. This situation gave rise to the category "Disarticulation of the disciplines of the Basic with the vocational cycle," which could be identified from observations of the students, such as the following:…”
Section: Resultssupporting
confidence: 63%
“…It was possible to obtain a critical arsenal of ideas from the students in the final stages of the Dentistry School as they identified critical points of their undergraduate course, especially with respect to the initial subjects that comprise the so-called "basic cycle". This basic cycle should be a comprehensive orientation to the profession, designed to help students develop attitudes and skills aimed at an understanding of actual professional demands and the process of scientific reflection and communication, consisting of a key moment designed to spark students' interest in the course or an opportunity to identify or seek other alternatives in their university education [3].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No ensino é importante que os professores busquem feedback de suas ações para transmitir segurança ao estudante para que este possa realizar um aprendizado consciente, significativo e reflexivo (FARIAS et al, 2015).…”
Section: º Blocounclassified